The Relationship Between Nutritional Status And Toddler Motor Development - Lumastari Ajeng Wijayanti; Rezqiqah Aulia Rahmat; Ratna Dewi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background : Nutritional status plays an essential role in children's growth and development . Adequate nutrition supports brain development , muscle growth , and motor development , whereas poor nutritional status may delay motor milestones . Objective : To determine the relationship between nutritional status and motor development among toddlers . Methods : A quantitative study using an analytical cross-sectional design was conducted among 60 toddlers aged 12–59 months selected through purposive sampling. Nutritional status was assessed using weight-for-age (WAZ) based on WHO standards , while motor development was evaluated using the Pre-Screening Developmental Questionnaire (KPSP) . Data were analyzed using descriptive statistics and the Chi- Square test . Results : Most toddlers had good nutritional status ( 70.0% ) and age-appropriate motor development ( 73.3% ). Statistics analysis showed a significant relationship between nutritional status and motor development ( p = 0.002 ). Conclusion : Nutritional status is significantly associated with motor development among toddlers . Children with good nutritional status are more likely to achieve appropriate motor development . Keywords : nutritional status, motor development , toddler , growth , KPSP